Enzymatic replacement in vitro of the first anticodon base of yeast tRNAAsp: application to the study of tRNA maturation in vivo, after microinjection into frog oocytes. - Carbon, P (1982)
A combination of several enzymes, RNase-T1, nuclease S1, T4-polynucleotide kinase and T4-RNA ligase were used to prepare and modify different fragments of yeast tRNAAsp (normal anticodon G U C). This allowed us to reconstitute, in vitro, a chimeric tRNA that has any of the four bases G, A, U or C, as the first anticodon nucleotide, labelled with (32p) in its 3' position. Such reconstituted (32p) labelled yeast tRNAAsp were microinjected into the cytoplasm or the nucleus of the frog oocyte and checked for their stability as well as for their potential to work as a substrate for the maturation (modifying) enzymes under in vivo conditions. Our results indicate that the chimeric yeast tRNAsAsp were quite stable inside the frog oocyte. Also, the G34 was effectively transformed inside the cytoplasm of frog oocyte into Q34 and mannosyl-Q34; U34 into mcm5s2U and mcm5U. In contrast, C34 and A34 were not transformed at all neither in the cytoplasm nor in the nucleus of the frog oocyte. The above procedure constitutes a new approach in order to detect the presence of a given modifying enzyme inside the frog oocyte; also it provides informations about its cellular location and possibility about its specificity of interaction with foreign tRNA.